Herders' perceptions, practice, and problems of night grazing in the Sahel: Case studies from Niger - Ayantunde, Augustine A.; Williams, Timothy O.; Udo, H.M.J.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Keulen, H. van (2000)
A survey was conducted from February to June of 1997 among livestock herders in two villages of Niger, Kodey and Toukounous, on their perceptions, practice, and problems of night grazing. Cattle and sheep were the species that were taken out for night grazing by the herders. Small herd size and labour constraints were mentioned as the principal reasons for not practicing night grazing. Major benefits of night grazing included good body condition, herd growth, increased milk production, prevention of diseases, and reduction in herd mortality. Insecurity, difficulty in staying awake at night, labour constraints, and damage to crops by animals were given as problems of night grazing. According to the herders, grazing time (duration) during the day and night was shorter in the wet season than in the dry season. In the wet season animals were herded (followed and closely supervised by herders), whereas in the dry season, animals were mostly left to range freely in both villages. In general, children herded the animals during the day, while adults were responsible for night-time herding. Herders' perceptions on night grazing as regards animal production parameters such as weight development, water consumption, fecal output and feeding behaviour are consistent with available experimental results. Therefore, future technical research needs to recognize the constraints faced by herders and determine how to overcome them to improve technical and economic efficiency.